Digital Competencies Development in Higher Education Institutions: A Mixed Methods Research Study - Miroslava Tokovska; Tímea Š eben ZaŠ¥ková; č½ubica Jamborová (Emerging Science Journal, 2022)
Objective: Learning to teach at the higher education level is not a straightforward path in Slovakia, and there are fewer opportunities to learn how to teach at this level. The paper summarizes selected findings and proposals for improvements related to the implementation of measures in selected areas of higher education institutions (HEI). The aim of the paper was to explore digital competency development in higher education institutions and factors with regard to university lecturers that affect the quality of the educational process in the context of the overall quality of graduates and labor market requirements. In addition, our study aims to fill an information gap and provide original data useful in the process of digital competency development in higher education. Methods/Analysis: The study employed an exploratory mixed-methods design. The data for this study is based on a survey with 24 open and closed questions and an analysis of 46 final thesis studies. Findings: Both the qualitative statements of the university lecturers and the survey shed light on the following: (1) (Re)creation of motivational factors; (2) Potential development of digital competencies; and (3) Supporting innovation in higher education. The results led to consideration of the educational process quality at the level of the subject and the object of education. Novelty/Improvement: The results point to the importance of investment in technology. This is related to improved educational outcomes and sustainable innovation in higher education. Slovak national education policymakers should provide innovative ways to increase the development of digital competencies in higher education institutions through the Recovery Plan for Europe; providing investment in technology related to improved educational outcomes and the development of sustainable innovation in higher education will all help to raise the standard. Doi: 10.28991/ESJ-2022-SIED-011 Full Text: PDF